A Descriptive Analysis of Corporate Governance Mechanisms and Earnings Management in Palestine - Ali Aljadba; Nur Hidayah Laili; Norhaziah Nawai (Universitas Muhammadiyah Yogyakarta, 2024)
Vol 24, No 1